Isolated Microsporum Canis from a canine nasal cavity bearer of intranasal foreign body and Transmissible Venereal Tumor – Radiografic imaging and rinoscopy – case report - Rolemberg, D. S. [UNESP]; Toledo, G. N.; Reis, S. D.S.; Moreira, P. P. [UNESP]; Moraes, P. C. [UNESP] (FapUNIFESP (SciELO), 2023)
Rhinopathies diagnosis in small animals is challenging, especially regarding their etiology. Imaging exams are very valuable tools for diagnostic procedures. The objective here is to report a rare case of rhinitis by Microsporum canis in a 4-year-old male, SRD dog, sneezing and with chronic purulent nasal secretion two weeks after surgical correction of cleft palate, emphasizing the imaging tests importance for a final and assertive diagnosis. Skull radiographs revealed turbinate destruction and two soft tissue amorphous structures with radiopacity at nasal cavity. The presence of a foreign body in the left passage, soaked in mucopurulent secretion associated with fungal plaques, with firm texture were evidenced by rhinoscopy, and identified as M. canis colonies by microbiological examination. In association, red-brown hyperplastic areas biopsied via rhinoscopy were histologically diagnosed as transmissible venereal tumor. It is concluded that such infection can be reported as opportunistic, secondary to local immunosuppression by post-surgical foreign body and nasal TVT. This is the first case to report such a pathogen in the dog, making its insertion in the differential diagnosis of rhinopathies extremely valuable.
Microsporum canis isolado em cavidade nasal de canino portador de corpo estranho e tumor venéreo transmissível intranasal – imagens radiográficas e rinoscópicas – relato de caso
Keywords: canine; neorformation; rhinoscopy; ringworms; strange body